Penerapan pendidikan karakter pada siswa MIN Kota Blitar melalui program perkemahan Jum’at Sabtu - Laili, Azizatun Nurul (Maliki Interdisciplinary Journal, 2024)
Character education through camping activities Friday-Saturday Scout Movement of MIN Kota Blitar with KKM UIN Malang. Scouting activities are a non-formal education process held in the outdoors with basic principles and scouting methods. KKM UIN Malang attempts to take scouting as an object of character education because it is in accordance with the purpose of making scouting extracurricular activities mandatory by the government. This research uses direct observation in activities. In this activity, there are various activities to cultivate character such as setting up tents, cooking, and exploration activities. Each activity has its own character meaning, including discipline, independence, and responsibility.